Preparation method of stapler stapling LCP (Liquid Crystal Polymer) material
By using reinforcing agents in stapler booking LCP materials, LCP and reinforcing agents are polymerized again, which solves the problems of high cost and insufficient strength of existing materials, achieves a significant improvement in material strength and color uniformity, and satisfies the domestic market diversified needs.
Patent Information
- Application Number
- CN202411479297.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
Smart Images

Figure CN119350875A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polymer composite material, and in particular to a method for preparing a stapler stapler LCP material. Background Art
[0002] The stapler magazine is one of the core parts of surgical instruments, and the requirements are very high. It carries the nail pusher. When the instrument is working, as the nail pusher slider is pushed forward, it drives the nail pusher to move in the nail magazine hole. The nail pusher pushes the titanium nail to the nail seat, and the titanium nail is compressed and closed to achieve the suturing effect of the tissue. Therefore, the stapler should have good biocompatibility so as not to cause allergies and other adverse reactions. There are currently two main materials for staplers, high-temperature nylon and medical-grade LCP. However, the current product price is too high, and the cost pressure on domestic medical device customers is too great, so it has lost its competitiveness in China. The main reason is that there are no alternative materials in China, and there is only one dominant company, so there is no room for bargaining. Therefore, developing an alternative material or a more advanced material has great market value.
[0003] Carbon fiber is usually combined with epoxy resin, phenolic resin, polytetrafluoroethylene and the like to form composite materials. They not only maintain many of the advantages of FRP, but also have many properties that are better than FRP. The strength and elastic modulus of carbon fiber-epoxy composite materials exceed those of aluminum alloys and are close to those of high-strength steel, which completely makes up for the disadvantage of the small elastic modulus of FRP. Its application in the field of medical chemical materials is gradually becoming more widespread, but because the surface of carbon fiber is too smooth, the compatibility of carbon fiber when mixed with LCP is poor, so it is necessary to improve the preparation method of its composite material.
[0004] The demand for materials of medical stapler-stapling cartridges in the domestic market is small and the colors are diverse. Foreign materials cannot meet this demand and the after-sales service is not in place. The main reason is that they think the quantity is too small and are unwilling to cooperate with color modification. At the same time, the product strength is weak, because the stapler cartridges of domestic medical devices have been adjusted and the glue position has been reduced to only 0.65mm (such as Figure 1 (As shown in point Ⅰ in the middle), the strength of this position is already weak after the raw material is formed, which poses a quality risk.
[0005] Nowadays, during the flow of plastic melt, due to the difference in fluidity between glass fiber or carbon fiber and resin, and the different mass density, the two tend to separate. The glass fiber with low density floats to the surface, and the resin with high density sinks inside. At the same time, due to the friction and shear force of the screw, nozzle, runner and gate during the flow of plastic melt, it will cause local viscosity differences. When the plastic melt is injected into the cavity, the glass fiber will flow from the inside to the outside, contact with the cavity surface, and form "floating fibers". The floating fiber phenomenon now has a great impact on the strength, reliability and appearance of the material. In summary, it is very necessary for my country to develop an alternative, or even superior LCP composite material to meet various needs in my country, and it has a very broad market space and application prospects. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a method for preparing LCP material for stapler stapling.
[0007] Technical solution: A method for preparing LCP material for stapler stapling, wherein the LCP material prepared by the preparation method comprises: LCP resin, carbon fiber, reinforcing agent, and high temperature resistant color powder, wherein the reinforcing agent is a compound obtained by the reaction of di(triethanolamine)titanate diisopropyl and 5-hydroxyisophthalic acid; the preparation method comprises the following steps of preparing the LCP material:
[0008] S1. Preparation of enhancer: Weigh an appropriate amount of di(triethanolamine)titanate diisopropyl ester into a reaction vessel, add methanol to dissolve it, then add 5-hydroxyisophthalic acid thereto, heat to 80°C, stir and reflux for 4-5h, at which time the carboxyl group on 5-hydroxyisophthalic acid and the hydroxyl group on di(triethanolamine)titanate diisopropyl ester undergo esterification reaction, after the reaction is completed, adjust the pH to 6, then perform reduced pressure distillation, dry and set aside.
[0009] S2. Weigh the corresponding amount of high-molecular LCP resin according to the mass percentage of the formula, dry the pretreated carbon fiber, high-temperature resistant color powder and reinforcing agent to constant weight, and after drying, add them into the mixing tank at the same time and mix them evenly. At this time, in the molten state, the LCP resin and the reinforcing agent polymerize again, thereby increasing the original molecular weight, greatly improving the tensile strength and impact toughness, and at the same time, the bonding force between the LCP resin and the inorganic fiber is also greatly increased due to the increase in side chains. Drying before adding the materials is to prevent the material structure from becoming hollow, thereby reducing the strength of the material. At the same time, due to the high melting point of the LCP resin, high-temperature resistant color powder is used to prevent the pigment from being burned at high temperatures, making the processed color more uniform and beautiful;
[0010] S3, adding the mixed materials into a twin-screw extruder, performing melt blending, extruding into strips, and chopping.
[0011] S4. Use an Instron 6800 series desktop universal testing machine to test according to ASTM standards. Package after passing the test. The ASTM D638 test method is to apply tension to the specimen and measure various properties of the specimen under stress. This test is performed using a universal testing machine (also known as a tensile testing machine) at a speed of 1 to 500 mm / min until the specimen fails (yields or breaks). ASTM D638 can measure a variety of different tensile properties.
[0012] Preferably, the LCP material comprises, by weight percentage, 68% of LCP resin, 10-19% of carbon fiber, 12-21% of reinforcing agent, and 1% of high temperature resistant color powder.
[0013] Preferably, the mass percentage of LCP resin, carbon fiber and reinforcing agent is 6-7:1-2:1-2.
[0014] Preferably, the carbon fiber is a carbon fiber pretreated by soaking in concentrated sulfuric acid. The treatment process is: the prepared carbon fiber is first placed in concentrated sulfuric acid and soaked at a temperature of 50°C for 50 minutes, then washed with clean water, blown dry, and then dried. Although the strength of LCP resin is very high, it needs stronger strength in medical applications, because the surface of the carbon fiber is smooth and the compatibility with the LCP resin is poor, which makes the prepared composite material components unevenly distributed, resulting in its physical properties and chemical properties being unstable, thereby affecting the performance of the product prepared by the LCP composite material, and applying the liquid phase oxidation method, by soaking the carbon fiber in concentrated sulfuric acid, allowing the fiber surface to form groups such as carboxyl, increase the roughness of the carbon fiber surface, and enhance the bonding force with the resin, and it is not enough to simply enhance the bonding force of the two, because the fluidity of this polymer material is poor, so adding a reinforcing agent to increase its fluidity can make it more uniform when melt-mixed, thereby improving the strength of the composite material and making the color more uniform.
[0015] Preferably, the mass ratio of diisopropyl di(triethanolamine)titanate to 5-hydroxyisophthalic acid is 2:1-4:1.
[0016] Preferably, in step S3, the temperature of the extruder is 310-360° C., and the current passing through the extruder is: main motor current frequency:feed motor current frequency=25.47:10 (Hz).
[0017] Preferably, the high temperature resistant color powder is a mixture of color powder and lanthanum oxide, and the mass percentage thereof is 8.5:1.5.
[0018] Beneficial effects:
[0019] (1) The present invention adopts a special formula and formula ratio, mainly using a reinforcing agent to polymerize the high molecular weight LCP and the reinforcing agent again to obtain an LCP material with a higher molecular weight, thereby greatly increasing the strength of the material. At the same time, since the side chains of the LCP molecules are greatly increased, the binding force between the inorganic fiber and the LCP resin is enhanced, making the physical properties of the material more reliable. At the same time, the binding force between the inorganic pigment and the LCP resin is also enhanced, making the color more uniform and eliminating the floating fiber phenomenon.
[0020] (2) The present invention can meet the various demands for colors in China. The compounded high temperature resistant color powder can still have good dyeing properties at high temperatures. Different colors can be prepared according to customer requirements, and the colors are uniform without floating fibers. At the same time, LCP uses domestically developed LCP resin, a new type of alternative material developed, and its excellent cost performance will provide strong supply guarantee and competitiveness for domestic medical companies. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a stapler of a medical stapler in the prior art. DETAILED DESCRIPTION
[0022] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0023] Example 1
[0024] Pretreatment of carbon fiber:
[0025] Weigh 300g of carbon fiber and put it into concentrated sulfuric acid, heat it to 50℃, take it out after 50 minutes, wash it with clean water, dry it, put it into a vacuum drying oven, set the temperature to 80℃, and dry it overnight. Set aside.
[0026] Preparation of enhancer:
[0027] Weigh 400g of di(triethanolamine)titanate diisopropyl ester into a reaction container, add methanol to dissolve it, then add 100g of 5-hydroxyisophthalic acid, heat to 80°C and stir to react for 3-4h. Pay attention to controlling the reaction time. After the reaction is completed, adjust the pH to 6, then perform reduced pressure distillation, and dry for later use.
[0028] Weigh 680g LCP resin, 160g pretreated carbon fiber, 159g reinforcing agent, and 10g high temperature resistant color powder respectively. Dry the LCP resin, pretreated carbon fiber, high temperature resistant color powder, silane coupling agent, and high flow aid to constant weight, and then add them to the mixing tank and mix them evenly.
[0029] The mixed materials were added into a twin-screw extruder, and the temperature of the extruder was set to 320°C, and the current of the extruder was: main motor current frequency: feed motor current frequency = 25.47:10 (Hz). The materials were melt-blended, extruded into strips, and chopped.
[0030] The strength of the material was tested using an Instron 6800 series desktop universal testing machine in accordance with ASTM standards.
[0031] Example 2
[0032] Pretreatment of carbon fiber:
[0033] Weigh 320g of carbon fiber and put it into concentrated sulfuric acid, heat it to 50°C, take it out after 50 minutes, wash it with clean water, dry it, put it into a vacuum drying oven, set the temperature to 50°C, and dry it overnight. Set aside.
[0034] Preparation of enhancer:
[0035] Weigh 400g of di(triethanolamine)titanate diisopropyl ester into a reaction container, add methanol to dissolve it, then add 200g of 5-hydroxyisophthalic acid, raise the temperature to 80°C and stir to react for 3-4h. Pay attention to controlling the reaction time. After the reaction is completed, adjust the pH to 6, then perform reduced pressure distillation, and dry for later use.
[0036] Weigh 680g LCP resin, 160g pretreated carbon fiber, 159g reinforcing agent, and 10g high temperature resistant color powder respectively. Dry the LCP resin, pretreated carbon fiber, high temperature resistant color powder, silane coupling agent, and high flow aid to constant weight, and then add them to the mixing tank and mix them evenly.
[0037] Add the mixed materials into a twin-screw extruder, set the temperature of the extruder to 310-360°C, and the current frequency of the extruder to: main motor current frequency: feed motor current frequency = 25.47:10 (Hz), perform melt blending, extrude into strips, and chop.
[0038] The strength of the material was tested using an Instron 6800 series desktop universal testing machine in accordance with ASTM standards.
[0039] Example 3
[0040] The same as Example 1, except that the pretreated carbon fiber prepared in Example 1 is replaced by carbon fiber that has not been pretreated.
[0041] Example 4
[0042] Same as Example 1, except that the reinforcing agent prepared in Example 1 is not present.
[0043] The high-strength LCP composite material prepared in Examples 1-4 was added to an extruder for extrusion molding to prepare a test plate, and five groups of tensile strength and flexural strength values were measured respectively, and the average values were calculated for comparison. The calculation formula is: Rm = (R1 + R2 + R3 + R4 + R5) / 5, (R1 ~ R5 are the tensile strength or flexural strength values tested in a single time). Then the color of the test plate was observed and the mechanical properties of the test plate were measured. The measurement results are shown in Table 1.
[0044] Table 1 Color of the test plate and the results of measuring the mechanical properties of the test plate
[0045]
[0046] As shown in Table 1, the average bending strength of the LCP resin composite material prepared in Example 1 reaches 293.2 MPa, and the surface color of the test plate is uniform, so the physical properties of this alternative Johnson's LCP are tested and compared with the original Johnson's material.
[0047] The comparative data are shown in the following table
[0048]
[0049]
[0050] Since the carbon fiber after oxidation in Example 1 produces a large number of carboxylic acid and other groups, the compatibility between the carbon fiber and the LCP resin is effectively improved, and the reinforcing agent and the LCP resin molecules are polymerized again, and the molecular weight is increased while the side chain of the molecule is further increased, thereby effectively improving the binding ability of the LCP resin with the carbon fiber and the inorganic pigment. At the same time, the high temperature resistant toner used in Example 1, under the high temperature environment of the material melting, the color is still not damaged. In Example 2, the ratio of di(triethanolamine)titanate diisopropyl ester and 5-hydroxyisophthalic acid is changed, but its strength is slightly reduced, but the change is very small. In Example 3, the carbon fiber is not oxidized, resulting in its compatibility with LCP is not high. Therefore, the material strength of this embodiment is reduced compared with Example 1. However, due to the use of the reinforcing agent, a certain strength is still retained. In Example 4, the reinforcing agent is not used, so that the material has extremely poor fluidity when melting, and the dyeing situation is extremely unstable, so its color is uneven, which belongs to an unqualified product. When compared with the existing materials, it can be clearly seen that both the strength and other physical properties have been greatly improved. In summary, the material obtained by the formula of the present invention has higher strength, more uniform color, and better meets the requirements.
[0051] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing LCP material for stapler stapling, characterized in that: The LCP material prepared by the preparation method comprises: LCP resin, carbon fiber, reinforcing agent, and high temperature resistant color powder, wherein the reinforcing agent is a compound obtained by reacting di(triethanolamine)titanate diisopropyl and 5-hydroxyisophthalic acid; the preparation method comprises the following steps of preparing the LCP material: S1. Preparation of enhancer: weigh an appropriate amount of di(triethanolamine)titanate diisopropyl ester and add it to a reaction container, add methanol to dissolve it, then add 5-hydroxyisophthalic acid thereto, heat to 80°C, stir and reflux for reaction for 4-5h, after the reaction is completed, adjust the pH to 6, then perform vacuum distillation, dry and set aside; S2, drying the LCP resin, the pretreated carbon fiber, the reinforcing agent and the high temperature resistant color powder to constant weight, and then adding them into a mixing tank and mixing them evenly; S3, adding the mixed materials into a twin-screw extruder, performing melt blending, extruding into strips, and chopping; S4. Testing the material obtained in step S3, and packaging it after it passes the test.
2. The method for preparing LCP material for stapler according to claim 1, characterized in that: The LCP material includes, by weight percentage, 68% LCP resin, 10-19% carbon fiber, 12-21% reinforcing agent, and 1% high temperature resistant color powder.
3. The method for preparing LCP material for stapler according to claim 1, characterized in that: The mass percentages of LCP resin, carbon fiber and reinforcing agent are 6-7:1-2:1-2.
4. The method for preparing LCP material for stapler according to claim 1, characterized in that: Carbon fiber is carbon fiber that has been pretreated by soaking in concentrated sulfuric acid.
5. The method for preparing LCP material for stapler according to claim 1, characterized in that: The mass ratio of di(triethanolamine)titanate diisopropyl to 5-hydroxyisophthalic acid is 2:1-4:
1.
6. The method for preparing LCP material for stapler according to claim 1, characterized in that: In step S3, the temperature of the extruder is 310-360°C, and the current frequency passing through the extruder is: main motor current frequency: feed motor current frequency = 25.47:10 (Hz).
7. The method for preparing LCP material for stapler according to claim 1, characterized in that: The high temperature resistant color powder is a mixture of color powder and lanthanum oxide, and the mass percentage thereof is 8.5:1.5.